Analisis Pengaruh Struktur Modal, dan Likuiditas terhadap Profitabilitas pada Perusahaan Sektor Otomotif di indonesia - Richky Prabowo; Aftoni Sutanto (Jurnal Samudra Ekonomi dan Bisnis, 2019)
This study is aims to determine the effect of capital structure and liquidity on profitability in automotive sector companies in Indonesia.This research is a non-participant observation research using quantitative data from secondary party as its instrument. The population in this research is automotive sector company in Indonesia.The capital structure variable in this study is measured by Debt to Equity Ratio (DER), the liquidity variable is measured by Current Ratio (CR), and the profitability variable is measured by Return on Assets (ROA).The sampling technique on this research is using Purposive Sampling, that is a sample determination technique using certain consideration. The sample used in this research is 11 companies. Observation period of this research is from 2012 to 2016.The classical assumption test of the instrument is using the test of normality, multicollinearity, autocorrelation, and heteroscedasticity. The analysis technique used in this research is multiple regression analysis technique.The results showed that the variable of DER (X1) has a significant effect on ROA (Y) in automotive companies in Indonesia. CR (X2) variable has a significant effect to ROA (Y) in automotive company in Indonesia. Then DER (X1) and CR (X2) this two variable both together have a significant effect on dependent variable of ROA (Y) on automotive company in Indonesia.